Development of E-Procurement System to Reduce the Non-Compliant Work Behavior in Purchasing - Munira Hanis Mokter, Nur; Nurul Hayatie Ishak, Siti; Razali, Suriyati (International Journal of Engineering and Technology, 2018)
E-procurement has been widely used as a tool to manage purchase and sale of goods or services between the company and the suppliers among multinational companies and government sectors. But, there are many small and medium enterprise companies still uses traditional procurement method to manage their suppliers. Maverick buying issues had been a major concern among business and the solutions for it still not clear. Therefore, the aim of this project is to identify the current process and system requirements in the procurement activities and to design and develop an e-procurement system to reduce the maverick buying. This system has been developed in accordance to rapid application development (RAD) methodology which consists of four phases which are requirements planning, user design, construction and cutover. The functionality and usability testing were then conducted with three (3) experts and thirty (30) respondents to evaluate the system based on the interface design, usability, efficiency, ease of use, user experience and satisfaction. As a result, the construct with the highest mean, 4.5 (SD = 0.57) whereby the user is satisfied with the interface of the system. To sum up, this system simplifies the traditional procurement process especially on the acquisition of suppliers and help in reducing maverick buying in terms of purchasing power.Â Â